Effect of organic and inorganic nitrates on cerebrovascular pulsatile power transmission in patients with heart failure and preserved ejection fraction. (20th April 2018) - Londono-Hoyos, Francisco; Zamani, Payman; Beraun, Melissa; Vasim, Izzah; Segers, Patrick; Chirinos, Julio A
Abstract: Objective : Increased penetration of pulsatile power to the brain has been implicated in the pathogenesis of age-related cognitive dysfunction and dementia, a common comorbidity in patients with heart failure and preserved ejection fraction (HFpEF). However, there is a lack of knowledge on the effects of organic and inorganic nitrates administration in this population on the power carried by pressure and flow waves traveling through the proximal aorta and penetrating the carotid artery into the brain microvasculature. Approach : We assessed aortic and carotid hemodynamics non-invasively in two sub-studies: (1) at baseline and after administration of 0.4 mg of sublingual nitroglycerine (an organic nitrate; n = 26); and (2) in a randomized controlled trial of placebo (PB) versus inorganic nitrate administration (beetroot-juice (BR), 12.9 mmol NO3 ; n = 16). Main results : Wave and hydraulic power analysis demonstrated that NTG increased total hydraulic power (from 5.68% at baseline to 8.62%, P = 0.001) and energy penetration (from 8.69% to 11.63%; P = 0.01) from the aorta to the carotid, while inorganic nitrate administration did not induce significant changes in aortic and carotid wave power (power: 5.49%PB versus 6.25%BR, P = 0.49; energy: 8.89%PB versus 10.65%BR, P = 0.27). Significance : Organic nitrates, but not inorganic nitrates, increase the amount of hydraulic energy transmitted into the carotid artery in subjects with HFpEF. These findings may have implications for the adverse effect profiles of these agents (such as the differential incidence of headaches) and for the pulsatile hemodynamic stress of the brain microvasculature in this patient population.